A multidisciplinary approach to triage patients with breast disease during the COVID‐19 pandemic: Experience from a tertiary care center in the developing world. Issue 1 (13th January 2021) - Sattar, Abida K.; Shahzad, Hania; Jabbar, Adnan Abdul; ValiMohammed, Azmina T.; Khan, Sadaf; Vellani, Yasmin; Idrees, Romana; Ali, Nasir; Masroor, Imrana; Saeed, Humera; Lakhani, Gulzar; Ayoub, Nadia; et al.
Abstract: Background: The COVID‐19 pandemic has created a need to prioritize care because of limitation of resources. Owing to the heterogeneity and high prevalence of breast cancers, the need to prioritize care in this vulnerable population is essential. While various medical societies have published recommendations to manage breast disease during the COVID‐19 pandemic, most are focused on the Western world and do not necessarily address the challenges of a resource‐limited setting. Aim: In this article, we describe our institutional approach for prioritizing care for patients presenting with breast disease. Methods and results: The breast disease management guidelines were developed and approved with the expertise of the Multidisciplinary Breast Program Leadership Committee (BPLC) of the Aga Khan University, Karachi, Pakistan. These guidelines were inspired, adapted, and modified keeping in view the needs of our resource‐limited healthcare system. These recommendations are also congruent with the ethical guidelines developed by the Center of Biomedical Ethics and Culture (CBEC) at the Sindh Institute of Urology and Transplantation (SIUT), Karachi. Our institutional recommendations outline a framework to triage patients based on the urgency of care, scheduling conflicts, and tumor board recommendations, optimizing healthcare workers' schedules, operating room reallocation, and protocols. We also describe the "Virtual Blended Clinics", a resource‐friendly means of conducting virtual clinics and a comprehensive plan for transitioning back into the post‐COVID routine. Conclusion: Our institutional experience may be considered as a guide during the COVID‐19 pandemic, particularly for triaging care in a resource‐limited setting; however, these are not meant to be universally applicable, and individual cases must be tailored based on physicians' clinical judgment to provide the best quality care.